The Construction of Homosexuality in New Zealand Judicial Writing - Clark, Edward (Victoria University of Wellington Law Review, 2006)
This article examines the language used by New Zealand judges to describe homosexuality. It analyses the use of such language in judgments delivered after the decriminalisation of homosexual intercourse in 1986, examining the effect that judicial language has on rights claims made by homosexuals. The article argues that a significant number of judges are careless or ill-informed in the language they use to refer to homosexuality and that the language used reinforces and repeats a number of negative stereotypes about homosexuality, constructing it as inferior to a heterosexual norm. This article criticises such careless or prejudiced language as incompatible with New Zealand’s human rights commitments and argues that this language constitutes a barrier to the full enjoyment of citizenship by homosexual New Zealanders.